2003
DOI: 10.1371/journal.pbio.0000005
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome of the Intraerythrocytic Developmental Cycle of Plasmodium falciparum

Abstract: Plasmodium falciparum is the causative agent of the most burdensome form of human malaria, affecting 200–300 million individuals per year worldwide. The recently sequenced genome of P. falciparum revealed over 5,400 genes, of which 60% encode proteins of unknown function. Insights into the biochemical function and regulation of these genes will provide the foundation for future drug and vaccine development efforts toward eradication of this disease. By analyzing the complete asexual intraerythrocytic developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

152
1,836
5
12

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,513 publications
(2,049 citation statements)
references
References 66 publications
152
1,836
5
12
Order By: Relevance
“…Although the in vivo phosphorylation status of these DNA replication components remains to be investigated, it is tempting to speculate that Pfmrk-mediated phosphorylation of PfRFC-5 and PfMCM6 may regulate the initiation of DNA replication. The microarray data of Pfmrk, PfMAT1 and Pfcyc-1 suggest high levels of expression from 4 to 28 h peaking at 8 and 24 h-several hours before the start of DNA replication [59]. PfMCM6 protein has been predominantly detected in late trophozoites and schizonts, and gene expression of both PfMCM-6 and PfRFC-5 peaks in late trophozoites through early schizonts-stages where most DNA replication is thought to occur [31,60].…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo phosphorylation status of these DNA replication components remains to be investigated, it is tempting to speculate that Pfmrk-mediated phosphorylation of PfRFC-5 and PfMCM6 may regulate the initiation of DNA replication. The microarray data of Pfmrk, PfMAT1 and Pfcyc-1 suggest high levels of expression from 4 to 28 h peaking at 8 and 24 h-several hours before the start of DNA replication [59]. PfMCM6 protein has been predominantly detected in late trophozoites and schizonts, and gene expression of both PfMCM-6 and PfRFC-5 peaks in late trophozoites through early schizonts-stages where most DNA replication is thought to occur [31,60].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analyses demonstrated that PfGluPho is expressed at a high level throughout the intraerythrocytic cycle of Plasmodium without showing stage-dependent differences (66,67).…”
Section: P Falciparum's G6pdmentioning
confidence: 99%
“…1 A brief description of the Plasmodium falciparum (the most lethal malarial parasite) life cycle is required to better understand its molecular interactions in invasion. Following the bite of a malarial parasite-infected mosquito, the inoculated sporozoites (larva-like parasites present in the mosquito's salivary glands) migrate to the liver and invade hepatocytes through the interaction of a yet unknown large number of proteins [2][3][4] [step a in Figure 1A].…”
Section: Rationale For Multiantigenic Multistage Vaccine Developmentmentioning
confidence: 99%